2018
DOI: 10.1111/bph.14328
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin analogues and nitric oxide contribution in the treatment of ocular hypertension and glaucoma

Abstract: In patients with ocular hypertension or glaucoma, all treatments aim to lower intraocular pressure (IOP) by modulating aqueous humour (AH) production and/or uveoscleral and trabecular meshwork/Schlemm's canal AH drainage. PG analogues are considered to be the 'gold standard' treatment and are the most frequently used IOP-lowering agents. Recent data support an important role for NO in regulating IOP. Thus, novel PG analogues carrying a NO-donating moiety were recently advanced. Latanoprostene bunod (LBN) and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…Latanoprostene bunod is hydrolyzed by corneal esterases to the prostanoid FP receptor agonist latanoprost acid (active metabolite) and butanediol mononitrate, which is further metabolized to 1.4-butanediol and nitric oxide (NO) (active metabolite) ( 8 ). Latanoprost acid increases matrix metalloproteinase (MMP)-1, MMP-3, and MMP-9 expression in the ciliary muscles, promoting the remodeling of the extracellular matrix and, subsequently, increases aqueous humor outflow through the uveoscleral pathway ( 8 , 9 ). The efficacy of timolol ophthalmic solution in the reduction of IOP has also been reported ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Latanoprostene bunod is hydrolyzed by corneal esterases to the prostanoid FP receptor agonist latanoprost acid (active metabolite) and butanediol mononitrate, which is further metabolized to 1.4-butanediol and nitric oxide (NO) (active metabolite) ( 8 ). Latanoprost acid increases matrix metalloproteinase (MMP)-1, MMP-3, and MMP-9 expression in the ciliary muscles, promoting the remodeling of the extracellular matrix and, subsequently, increases aqueous humor outflow through the uveoscleral pathway ( 8 , 9 ). The efficacy of timolol ophthalmic solution in the reduction of IOP has also been reported ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that prostaglandins (PGs) are involved in various physiological and pathological functions such as regulation of smooth muscles, inflammation, immune response, and others 1 . Camras et al first reported that the topical administration of PGF2α and PGE2 decreases intraocular pressure (IOP) in rabbits, and suggested that the stimulation of the prostanoid FP receptors and PGE2 receptors (mainly EP2 and EP3) represent a potentially novel therapy for the treatment of patients with ocular hypertensive (OH) and glaucoma 2 .…”
mentioning
confidence: 99%
“…Clinical studies have shown that patients on bimatoprost frequently develop ocular hyperemia 43‐46 . This effect of bimatoprost 0.03% on OS has been confirmed to be due to vasodilation mediated via over‐production of nitric oxide synthase, but not due to the induction of inflammatory cytokines 43,47 …”
Section: Discussionmentioning
confidence: 94%